Iterative versus standard deferred acceptance: Experimental evidence - Inácio Bó; Rustamdjan Hakimov (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
We run laboratory experiments where subjects are matched to colleges, and colleges are not strategic agents. We test the Gale-Shapley Deferred Acceptance (DA) mechanism versus the Iterative Deferred Acceptance Mechanism (IDAM), a matching mechanism based on a new family of procedures being used in the field, in which information about tentative allocations is provided while students make choices. We consider two variations of IDAM: one in which they are only informed about whether they are tentatively accepted or not (IDAM-NC) and one in which students are additionally informed at each step of the tentative cutoff values for acceptance at each school (IDAM). A significantly higher proportion of stable outcomes is reached both under IDAM and IDAM-NC than under DA. The difference can be explained by a higher proportion of subjects following an equilibrium strategy akin to truthful behavior under IDAM and IDAM-NC than truthful behavior itself under DA. Moreover, the provision of intermediate cutoff values in IDAM leads to higher rates of equilibrium behavior than in IDAM-NC and a higher robustness of stability between the rounds of experiments. Our findings provide substantial support for the rising practice of using iterative mechanisms in centralized college admissions in practice.
Keywords: C78; C92; D63; D78; D82; 330; Market Design; Matching; Iterative Mechanisms; College Admissions; Experiments